The Representation of Creativity Values in the Indonesian ELT Textbook in twelfth Grade of Senior High School Students: A Content Analysis - Nur Lailatul Farihah (Faculty of Education, 2025)
This study explores the representation of creativity values in the Indonesian ELT textbook for twelfth-grade senior high school students, emphasizing the importance of creativity as a core element of character education and 21st-century skills. The research is driven by the concern that, although textbooks play a crucial role in shaping learners' competencies, creativity is often underrepresented or insufficiently integrated. By analyzing how creativity is conveyed through the textbook's visual and verbal content, this study highlights the need for more holistic and innovative pedagogical approaches in Indonesian EFL classrooms.
Supervisor 1 Drs. Bambang Suharjito, M.Ed. Supervisor 2 Ika Fitriani, S.Pd. M.Pd.
Keywords: Representation; Creativity Values; Indonesian ELT Textbook